LPIC-1 (Exam 101) : Linux Professional Institute Certification Exam 101 : video - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2015)
LPIC-1 (Exam 101) LiveLessons offers hours of training to help you pass the LPIC-1 (Exam 101) certification. LPIC-1 (Exam 101) LiveLessons is a unique video product that provides a solid understanding of all topics candidates need to master to pass the LPIC-1 (Exam 101) Certification. This course offers 14 lessons that cover all topics as mentioned in the LPI objectives as published on www.lpi.org. This course doesn't just offer a preparation for the LPI 101 exam–it can also serve as an introduction for people who want to learn basic Linux administration skills. The videos provide thorough coverage of command-line skills that work on multiple distributions, and prepares anyone to acquire more in-depth knowledge of common Linux administration tasks.